PENGARUH LEVERAGE, PROFITABILITAS, DAN GOOD CORPORATE GOVERNANCE TERHADAP FINANCIAL DISTRESS (Studi Kasus pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2016) - Affiah, Alissa; Muslih, Muhamad (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan dan Akuntansi, 2018)
This study aims to determine the effect of Leverage, Profitability, and Good Corporate Governance to Financial Distress in mining sector companies listed on Indonesia Stock Exchange 2012-2016 either simultaneously or partially. The method in this research is quantitative research method. The method of analysis used in this research is logistic regression analysis using SPSS 21 software. Based on the result of this research, the result of the combination of independent variables consisting of leverage, profitability, and good corporate governance can explain or influence the dependent variable that is financial distress is 63.6% and the rest of 36.4% is explained by other factors outside the research. The results of this study also show that leverage, profitability, and good corporate governance have a significant simultaneous effect on financial distress. Partially, leverage, independent board of commissioners, and institutional ownership have no significant effect on financial distress, profitability and managerial ownership having a significant effect on financial distress in a negative direction.Â Keywords: Leverage, Profitability, Good Corporate Governance, Financial Distress.